Answer this step by step this question will give ur answer a expert verification the green tick on ur answer Wrong answer will be reported
Attachments:
![](https://hi-static.z-dn.net/files/d51/c90568e707b6015a994adb4de502da47.jpg)
Answers
Answered by
15
= 28^3+(-15)^3+(-13)^3
=> If a+b+c =0 ,then we can do it by 3abc
(we are not taking powers i.e. a=28,b=-15,c=-13)
=28+(-15)+(-13)
=28-15-13
=0
=> 3abc
=3(28)(-15)(-13)
=16380
Answered by
2
Answer:
16380
Step-by-step explanation:
SOLUTION
BRAINLIEST BUDDY
Similar questions